(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Parenting is an approach to raising children into healthy adults in terms of physical, psychological, and social aspects. Purpose: The present piece of study is aimed to measure the difference in various dimensions of emotional intelligence and resilience between children raised by authoritative and authoritarian parents. Methods: To achieve the objective of the study, a sample of children (N = 117) reared with authoritative (n = 69) and authoritarian parenting styles from (n = 48) were collected through Non-probability (Purposive) sampling method. Moreover, to obtain the data following psychological tools such as the Parenting Authority Questionnaire (Buri,1991), Emotional Intelligence Scale and Resilience Scale were used. Results: The outcomes of the study revealed higher scores for children on emotional intelligence viz., Managing their own emotions among children of authoritative parents when associated with authoritarian parenting style. Likewise, children raised with authoritative parenting styles scored higher on resilience viz., personal resilience when compared with authoritarian parenting style. Conclusion: It may be concluded that various approaches of parenting have a significant impact on emotional intelligence and resilience making them emotionally aware to manage one’s emotions as well as others and also help them develop psychologically resilient to deal with the stressors of life.